Perception of the implementation of the environmental management system in universities: A case study in a public university - Alva Tuesta, Judith Nathaly; Cruz Caro, Omer; Chávez Santos, River; Sánchez Bardales, Einstein; Carrasco Rituay, Angelica Maria; Maicelo Rubio, Yecenia del Carmen (Heritage and Sustainable Development, 2024)
The environmental management system (EMS) is a structured framework that entities use to manage environmental impacts, ensure compliance with regulations, and incorporate sustainability initiatives. For this reason, the study aims to identify the level of perception regarding implementing the EMS in universities. For this purpose, a study with a mixed approach has been carried out, in a sample composed of 321 students, 114 teachers, 190 administrators, 33 researchers, and 5 university authorities. The results show that the perception of the level of implementation of the EMS is at a medium level, evidencing weaknesses in institutional, pedagogical, investigative, and social responsibility management. This situation shows the lack of training activities, awareness campaigns, and educational programs that allow the adequate development of environmental skills and culture in all university community members. The lack of participation and involvement in institutional environmental management could seriously harm the effectiveness of the university's EMS, which would compromise the fulfillment of its environmental objectives and goals, as well as its commitment to sustainable development and environmental protection.